On Generalized Sierpiński Graphs - Rodríguez-Velázquez Juan Alberto (Discussiones Mathematicae Graph Theory, 2017)
In this paper we obtain closed formulae for several parameters of generalized Sierpiński graphs S(G, t) in terms of parameters of the base graph G. In particular, we focus on the chromatic, vertex cover, clique and domination numbers.